Obtenção de carvão ativado a partir da fuligem da candeia por diferentes processos de ativação - Gomes, Pedro Barroso (2017)
In the present work candeia’s soot (FC), an agroindustrial waste, was used as a precursor to obtain activated charcoal (CA). For this, different activation methodologies described in the literature were evaluated, as well as an innovative activation with iron oxide. The main objective of this work was to evaluate the possibility of obtaining activated charcoal from the candeia’s soot, as well as a comparison between the activation processes. The activation conditions used were based on methodologies found in the literature, involving activation with NaOH, H3PO4, ZnCl2, CO2 and Fe2O3. The activated charcoals obtained were characterized by different techniques such as elemental analysis (CHN), thermogravimetric analysis (TGA), infrared spectroscopy (IV-TF), specific surface area, scanning electron microscopy (SEM), pH of zero charge (pHpcz) and Boehm titration. Adsorption studies were performed using the methylene blue (AM) and reactive black (PR) dyes. The characterizations have proven to obtain activated charcoals with different characteristics depending on the activation process. From CHN and TG analyzes it is possible to know that the activated charcoals have carbon content between 70 and 85%. By the use of infrared spectroscopy and Boehm titration show a quantitative variation in the functional groups, observed according to each methodology used, also presenting variation related to the pHpcz point. The morphology evaluated by SEM showed a great distinction between the materials, resulting in an apparent decrease of the particles or ruptures in the structure, in relation to the precursor. The obtained results of specific surface area show that the activated charcoals activated with NaOH and Fe2O3 show the highest values (804 and 435 m 2 g -1 , respectively). These coals also had the best results for adsorption of the dyes AM and PR, reaching to adsorb about 222 and 360 mg g -1 , respectively. The adsorption processes were considered favorable according to the evaluated parameters (RL and n). And the adsorption of the AM for the majority of the materials was better suited to the Langmuir model and pseudo-second order, whereas for the PR the most suitable models for almost all materials were Freundlich and pseudo-second order. The results show that the processes of activation of the candeia’s soot were very efficient using NaOH and Fe2O3 as activating agents, demonstrating viability in obtaining CA using FC as a precursor.